On energy-absorbing mechanisms and structural crashworthiness of laterally crushed thin-walled structures filled with aluminum foam and CFRP skeleton. (March 2021) - Zhu, Guohua; Zhao, Zhonghao; Hu, Po; Luo, Geng; Zhao, Xuan; Yu, Qiang
Abstract: In the present study, thin-walled tubes filled with aluminum foam and CFRP skeleton (FCFTs) are developed and manufactured based on a multiple material system. The structural crashworthiness of the proposed design is investigated under quasi-static lateral loading. Further, the aluminum tube, the foam-filled tube and the tubes filled with CFRP skeleton are also designed and tested to perform a comparative study. It is found that the FCFT-1 (the tube filled with foam and CFRP skeleton with square cells) exhibits superior SEA (specific energy absorption), which is almost five times that of the individual aluminum tube, and almost 10% higher than that of the foam-filled tube. However, FCFT-2 (the tube filled with foam and CFRP skeleton with triangular cells) provides relatively lower energy-absorbing capacity, as its aluminum tube generates several axial cracks during crushing process leading to low deformation level of the foams. Furthermore, crush simulations are conducted to better understand the energy-absorbing mechanisms of the FCFT-1. The numerical results demonstrate that the plastic deformation of the separated foams makes up the major part of the total energy absorption. Besides, the performance improvement of FCFT-1 can be partly attributed to the fact that the separated foams generate larger plastic deformation during crushing process. Apart from this, the increased interaction effects between the separated foams and the CFRP skeleton lead to a higher FE (frictional energy), which also makes a slight contribution to the performance improvement of FCFT-1. Finally, parametric studies are performed to explore the influences of design parameters on the crashworthiness characteristics of FCFT-1. It is indicated that the energy-absorbing capacity can be slightly improved by raising cell number, proportion of 45° layer or foam density. The present work is expected to provide some insights for researchers and engineers to design such structures for energy absorption applications. Highlights: Lateral crushing of thin-walled tubes filled with aluminum foam and CFRP skeleton (FCFTs) is investigated. Energy-absorbing mechanisms of FCFTs are explored. A parametric study is further conducted to explore the influences of design parameters.